Differential effects of omni-channel touchpoints and digital behaviors on digital natives' social cause engagement. Issue 3 (13th August 2018) - Dahl, Andrew J.; D'Alessandro, Anthony M.; Peltier, James W.; Swan, Eric L.
Abstract : Purpose: Social causes increasingly rely on omni-channel touchpoints involving personal discussions and grassroots digital marketing efforts to engage individuals via social referrals. This paper aims to examine digital natives' perceived effectiveness of omni-channel touchpoints for increasing social cause engagement including social media, digital media, traditional and interpersonal communications, along with an individual's social/digital media behaviors. Design/methodology/approach: The paper reports empirical results from an online survey of 924 digital natives. The paper uses multivariate and multiple regression analyses to examine the differential effects of a diverse range of media influencing the perceived effectiveness of social cause referrals from a family member versus a close friend. Findings: The results identify the combination of omni-channel touchpoints most likely to be effective for enhancing organ donation support and registration efforts as part of social referral campaigns. The findings suggest differences exist based on whether the campaign targets family members or friends. Research limitations/implications: The research focuses on digital natives and does not address differences that may vary by specific messages shared across generational groups or ethnicities. More research is also necessary, which examines the effects of digital consumption versus content creation behaviors. Practical implications: The paper includes implications for social marketers looking at increasing viral reach and engagement via social referral campaigns. Marketers should integrate the omni-channel touchpoints deemed to be most effective for each target based on specific campaign goals. Originality/value: This paper addresses a gap in marketers' understanding of how digital natives perceive social referral campaigns targeting their social circle via various omni-channel touchpoints.